Dhikr Therapy Strategy for Pessimistic Teenagers in Facing Family Problems: Remaja Pesimis Dalam Menghadapi Problem Keluarga - Puspasari, Karisma Dewi; Ma’rufah, Rima Wardatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The family is the smallest social unit that plays a vital role in supporting children’s physical, mental, and emotional development. However, family problems such as conflict, lack of communication, and disharmony can negatively impact adolescents, particularly leading to pessimism. Pessimism in adolescents is characterized by negative thinking patterns, low self-confidence, and a tendency to avoid challenges, ultimately reducing their psychological well-being. From an Islamic perspective, pessimism can weaken faith and trust in God, necessitating spiritual strategies to overcome it. One approach offered is dhikr therapy. This study used a descriptive qualitative method through library research, reviewing various literature related to family problems, pessimism in adolescents, and the application of dhikr therapy. The results of the study indicate that dhikr, whether in the form of morning and evening dhikr, istighfar (istighfar), shalawat (prayer), or dhikr hasbullah (God’s blessing), can provide inner peace, reduce anxiety, increase optimism, and strengthen mental resilience in adolescents. Thus, dhikr therapy can be an effective strategy in helping pessimistic adolescents face family problems, while strengthening their spiritual foundation and psychological well-being.